Cryopreservation of kernel and zygotic embryos of oil palm (Elaeis guineensis Jacq.) - Prakash, Krishna; Kumar, K. Sunil; Chaudhury, Rekha (Journal of Plantation Crops, 2019)
The seed storage behaviour of oil palm (Elaeis guineensis Jacq.) is enigmatic. Earlier, it was categorised as recalcitrant or orthodox and later, it was confirmed to be exhibiting intermediate seed storage behaviour. Considerable difference in the water content between zygotic embryo and the seed/kernel exists which is proportionally maintained even after desiccation of kernel, which qualifies it to be intermediate storage behaviour. To attempt long term conservation of oil palm germplasm grown in India, studies on germinability/viability in relation to moisture content was conducted for ‘dura’ palm using seed kernel, zygotic embryos and endosperm plug as explants. Based on desiccation and cryopreservation experiments in kernels and embryos, it showed intermediate storage behavior. Zygotic embryo cryopreservation was possible between the moisture content of 10-20 per cent of embryos, and was achieved using silica gel desiccation method of either kernels or embryos or both. Four hours of desiccation under laminar air flow was found optimum to maintain viability after cryo-exposure. A new type of explant, endosperm plug, of 0.1 g weight and 2-5 mm length could offer advantage for the desiccation and cryopreservation of oil palm as it could be dehydrated up to 6 per cent moisture level and retained 20 per cent viability after cryo-exposure. Initial attempt to use encapsulation-dehydration and vitrification-desiccation methods for embryos of oil palm did not yield positive results, necessitating further experiments.